Complete Mapping of DNA‐Protein Interactions at the Single‐Molecule Level. Issue 23 (5th October 2021) - Liu, Wenzhe; Li, Jie; Xu, Yongping; Yin, Dongbao; Zhu, Xin; Fu, Huanyan; Su, Xiaodong; Guo, Xuefeng
Abstract: DNA–protein interaction plays an essential role in the storage, expression, and regulation of genetic information. A 1D/3D facilitated diffusion mechanism has been proposed to explain the extraordinarily rapid rate of DNA‐binding protein (DBP) searching for cognate sequence along DNA and further studied by single‐molecule experiments. However, direct observation of the detailed chronological protein searching image is still a formidable challenge. Here, for the first time, a single‐molecule electrical monitoring technique is utilized to realize label‐free detection of the DBP–DNA interaction process based on high‐gain silicon nanowire field‐effect transistors (SiNW FETs). The whole binding process of WRKY domain and DNA has been visualized with high sensitivity and single‐base resolution. Impressively, the swinging of hydrogen bonds between amino acid residues and bases in DNA induce the dynamic collective motion of DBP–DNA. This in situ, label‐free electrical detection platform provides a practical experimental methodology for dynamic studies of various biomolecules. Abstract : A single‐molecule electrical detection platform, based on a silicon nanowire field‐effect transistors (SiNW FETs) nanocircuit, is applied to real‐time monitor the complete interaction process of WRKY1N and DNA with single‐base‐pair resolution. A long‐last collective motion correlated to the specific recognition site is observed at the single‐molecule level, providing a novel technique with single‐molecule/single‐event sensitivity to decipher the comprehensive mechanism of biomolecule interactions.